A Study on Appropriate Plant Diagram Synthesis for User-Suited HMI in Operating Control - Metzger, Mieczyslaw; Polaków, Grzegorz (Engineering Interactive Systems, 2008)
In this paper a study on appropriate plant diagram synthesis for user-suited HMI in operating control is presented. Discussion is based on the long-term personal experience and illustrated with excerpts of existing HMIs developed for research and industrial use. The HMI notion is defined for operating control and for operator training. The paper present three aspects of plant diagrams design. The first aspect deals with task-oriented usage of screen space for plant diagram and other GUI elements. Second aspect covers all methods of image creation for process diagrams, including photography, schematic diagrams, use of predefined normalised 3D graphical elements, and creative possibilities of 3D scene. The third aspect stresses capability of dynamic visualisation with the use of animated graphics.